Copy number variation (esv27061) in hypertensive young adults - Siti Radziah binti Shaik Alaudeen (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Hypertension is an established risk factor for cardiovascular diseases. Global estimate predicts one in four to suffer from hypertension while in Malaysia its overall prevalence among adults in 2015 was approximately 30%. Hypertension related morbidities and mortalities around the world also show gradual increase. These suggest for early detection and prevention. Lately, several reports and databases on genomic variants have associated variation in DNA sequences called copy number variation (CNV) with susceptibility to common diseases including hypertension. However, no report is available on the role of CNV in essential hypertension in Malaysia. Thus, this study for the first time aims to characterize the CNV esv27061 (located in chromosome 1p13.2) among normotensive, prehypertensive and mild hypertensive young adults in Malaysia. In this comparative cross-sectional study, 104 subjects living in Kuantan who gave voluntary consent to participate are recruited and divided into three groups: control (43 subjects), prehypertensive (38 subjects) and mild hypertensive (23 subjects). DNA for CNV determination was extracted from 3 ml of blood sample collected from each subject in the study. CNV esv27061 was analyzed using a cutting edge optimized droplet digital polymerase chain reaction (ddPCR) technique which has enhanced sensitivity and precision. The frequency distribution patterns among mild hypertensives showed significant peak gain particularly in copy numbers 3 and 5 while the prehypertensive subjects exhibited significant increase in copy numbers 4 and 5. This discovery for the first time emphasizes the importance of frequency patterns in determining CNV status of prehypertensive and mild hypertensive subjects. All the subjects in this study showed significantly low frequency for copy numbers 2, 6 and 7. Majority of subjects in control (n=38; 88.4%), prehypertensive (n=33; 86.8%) and mild hypertensive (n=21; 91.3%) showed gains (copy number > 2) while 11.6% of control, 13.2% of prehypertensive and 8.7% of mild hypertensive subjects exhibited normal copies (copy number = 2). At a significant P-value ≤ 0.05, it was observed that there is no statistically significant association between copy number variation CNV esv27061 status with normotensive, prehypertensive and mild hypertensive subjects. The present investigation found more gain in CNV esv27061 than loss which is consistent with Database of Genomic Variants (DGV). However, this study could not show significant association between CNV esv27061 status and blood pressure among the three groups of subjects studied. Importantly, the preliminary findings of the present study provide information regarding CNV esv27061 status among young adult hypertensives which may be crucial for future studies.